Pengaruh Gaya Kepemimpinan, Kompensasi dan Komitmen Organisasi Terhadap Kepuasan Kerja pada PT. Kresna Karya Basecamp Akah Klungkung - Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra (Journal Research of Management, 2024)
The aim of this research is to find out whether leadership style, compensation and organizational commitment have an effect on job satisfaction at "PT. Kresna Karya Basecamp Akah Klungkung". Samples were collected using saturated sampling techniques totaling 55 respondents. The data analysis technique used in this study was multiple regression analysis. The results of the study showed that: (a) there is a significant and positive effect between leadership style and job satisfaction with a coefficient value of 0.325 and a significance value of 0.001, (b) there is a significant and positive effect between compensation and job satisfaction with a coefficient value of 0.364 and a significance value of 0.000, and (c) there is a significant and positive effect between organizational commitment and job satisfaction with a coefficient value of 0.327 and a significance value of 0.005.